Alterations in Epithelial Cell Polarity During Endometrial Receptivity: A Systematic Review - Whitby, Sarah; Zhou, Wei; Dimitriadis, Evdokia (Frontiers in Endocrinology, 2020)
Background: Abnormal endometrial receptivity is one of the major causes of embryo implantation failure and infertility. The plasma membrane transformation (PMT) describes the collective morphological and molecular alterations occurring to the endometrial luminal epithelium across the mid-secretory phase of the menstrual cycle to facilitate implantation. Dysregulation of this process directly affects endometrial receptivity and implantation. Multiple parallels between these alterations to confer endometrial receptivity in women have been drawn to those seen during the epithelial-mesenchymal transition (EMT) in tumorigenesis. Understanding these similarities and differences will improve our knowledge of implantation biology, and may provide novel therapeutic targets to manage implantation failure. Methods: A systematic review was performed using the Medline (Ovid), Embase and Web of Science databases without additional limits. The search terms used were “(plasma membrane* or cell membrane*) and transformation*” and “endometrium or endometrial”. Research studies on the PMT or its regulation in women, discussing either the endometrial epithelium, decidualized stroma, or both, were eligible for inclusion. Results: A total of 198 articles were identified. Data were extracted from 15 studies that matched the inclusion criteria. Collectively, these included studies confirmed the alterations occurring to the endometrial luminal epithelium during the PMT are similar to those seen during the EMT. Such similarities included alterations to the actin cytoskeleton remodeling of adherens junctions, integrin expression and epithelial-stromal communication. These were also some differences between these processes, such as the regulation of tight junctions and mucins, which need to be further researched. Conclusions: This review raised the prospect of shared and distinct mechanisms existing in PMT and EMT. Further investigation into similarities between the PMT in the endometrium and the EMT in tumorigenesis may provide new mechanistic insights into PMT and new targets for the management of implantation failure and infertility.